Immobilization of Lipase from Candida Rugosa onto Selected Matrices for Use in Enantioselective Preparation of (-)-Menthyl Butyrate - Othman, Siti Salhah (2004)
Products of pure enantiomer are in great demand and have been receiving attentions since the past few decades. Reasons which make these products of interest are their efficacies and specificities compared to the racemic mixture or the other enantiomer, which is often inactive or exhibit toxicity. In recent years, enzymes are finding increasing acceptance as catalysts in the synthesis of these enantiomerically pure products due to their high enantioselectivity, commercial availability and environmental friendly reactions. In this study, among seven lipases tested, Candida rugosa lipase exhibited the best ability to catalyze the resolution of (±)-menthol in organic solvent. The lipase was immobilized on different carriers including a newly synthesized Mg/Al-hydrotalcite (HT), a kind of layered double hydroxide material prepared at molar ratio 4 of Mg: Al. Method of immobilization used was a simple physical adsorption method. Lipase immobilized on Amberlite XAD7, Eupergit C, Eupergit C 250 L and the newly synthesized hydrotalcite, exhibited highest enantioselectivity and activity, and was chosen for further characterization. Immobilization of lipase onto these supports was confirmed using a Scanning Electron Microscope (SEM). Native lipase was not easily dispersed and suffers dehydration of cell as a result of lyophilization. For the immobilized lipases, direct lipase-support interaction can be clearly viewed. Experiment was carried out in different organic solvents and at different water activities (aw). High yield (60 %) and optical purity (> 90 %) of the product was obtained in hexane with butyric anhydride as the acyl donor at 30 oC using Candida rugosa lipase immobilized on Amberlite XAD7. Yield of (-)- menthyl butyrate were found to be dependant on the water activity (aw = 0.33 – 0.53). Highest yield of (-)-menthyl butyrate (66 %) was achieved using Amberlite XAD7-lipase as catalyst after 60 hours of continuous reaction while highest production of (-)-menthyl butyrate using other immobilized lipases (35 – 60 %) was achieved after about 24 – 28 hours of incubation. The effects of various temperatures, storage conditions, stability in organic solvents and lipase reusability were investigated for their influence on the enzymatic enantioselective formation of (±)-menthyl butyrates. The immobilized lipases retained high catalytic activity (53 – 83 %) and show increased stability (2 – 3 folds) compared to the native lipase in all cases.Although lipase activity decreased as temperature is increased, immobilized lipase especially Eupergit C-lipase was least affected and showed highest activity (83 %) even upon incubation at 70 oC. During storage at different temperatures for 60 days, all lipases retained 100 % of their initial activity when stored at –20 oC. Their activities were found to decrease gradually as temperature was raised. When storage temperatures were raised to 0 and 4 oC, immobilized lipases exhibited 1.6 – 2.4 folds higher catalytic activities (62 – 87 %) than native lipase (35 – 39 %). Immobilized lipases showed slightly higher activities of 1 – 2 folds to the native lipase upon storage at room temperature (26.5 oC) for 60 days. In this study, interestingly, immobilized lipases were still active (relative activities of 46 – 61 %) even after ten days of incubation in hexane. In addition, their activities showed low effect, with 24 - 49 % decline in relative activities even after 5 cycles of washing with 20 mL of hexane. Furthermore, the immobilized lipases showed possible and efficient reuse with HT-lipase exhibiting excellent half life (t½) of 16 days. Other immobilized lipases, however, showed lower half-life, t½ = 3.5 for Amberlite XAD7-lipase and t½ = 9.0 for Eupergit C 250 L-lipase and Eupergit C-lipase.